Evaluation of the relationship between medications and falls among urban community dwellers in Malaysia / Anam Zia - Anam, Zia (2017)
Malaysia is labelled as an aging nation because of its rapidly expanding older population. Falls are the commonest cause of accidents, injuries, disability and death among the geriatric population. While older people are the highest users of medications; polypharmacy and “fall risk increasing drugs”(FRID) are widely related to falls. The falls prevention guidelines recommend medication reviews and FRID withdrawal among older fallers. We aimed to evaluate the association between medications and falls among older Malaysian urban community dwellers.This study was performed and analysed in 2sections; case control comparisons and prospective intervention study. The fallers were recruited as the participants aged ≥65years with ≥2falls or 1 injurious fall in the previous year who visited the primary care clinics, geriatric medicine clinics and the emergency department of a hospital. The non-fallers were the volunteers aged≥65 years with no falls over the past year. Case-control-comparisons were performed between fallers and non-fallers to assess the association between falls and FRID, possible mechanisms and mediators of FRID and the appropriateness of prescription drugs using STOPP2 criteria. A prospective study was performed to assess the feasibility and effectiveness of medication review as an intervention for fall prevention.We found that use of multiple FRID was associated with falls rather than polypharmacy or single FRID. Contrary to the previous preconceptions that antihypertensives are associated with falls through the mechanism of orthostatic hypotension; we found that antihypertensives were not associated with orthostatic hypotension or falls. Rather fallers had significantly lower standing systolic blood pressure obtained 2-3 minutes after standing. We observed that anticholinergic burden of drugs is associated with falls due to reduced physical performance exhibited by the deterioration in timed up and go and functional reach scores. We found that prescribing of potentially inappropriate iv drugs to older adults was significantly associated with falls; while polypharmacy, orthostatic hypotension and poorer timed-up-and-go scores were associated with potentially inappropriate prescriptions. In prospective study, out of 205 fallers with FRID, 98(47.8%) were randomized to intervention, and 107(52.2%) to conventional care, the medications were changed in 19(9.3%) participants of the intervention group. There was no significant difference in falls outcomes among the fallers with FRID regardless of whether they received medication review. While our study is the first assessment of the role of medications in falls in Malaysia, it uniquely found that the presence of multiple FRID, anticholinergic burden even with the lowest score and potentially inappropriate prescriptions instead of single FRID or polypharmacy are associated with falls. Furthermore, instead of antihypertensives or orthostatic hypotension, a lower standing systolic blood pressure is associated with falls. The positive association between anticholinergic score and falls is mediated by gait and balance impairment. An attempt to reduce FRID burden via medication review remains unsuccessful as it is not feasible to withdraw FRID without affecting patient’s disease management. While future research is needed to consolidate our findings, our prospective study may serve as a pilot of a larger randomized controlled study evaluating the usefulness and longer term effects of medication reviews in addressing falls.